Global Analysis of Electric Vehicle Charging Infrastructure and Sustainable Energy Sources Solutions - Sihem Nasri; Nouha Mansouri; Aymen Mnassri; Abderezak Lashab; Juan Vasquez; Hegazy Rezk (World Electric Vehicle Journal)
Recently, the rapid increase in the adoption of electric vehicles (EVs) has been driven by considerable technological advancements and a growing focus on environmental sustainability. As consumers and governments increasingly recognize EVs as a viable alternative to traditional internal combustion engine vehicles, the demand for a reliable and accessible charging infrastructure has surged. However, establishing a robust network of charging stations is no longer crucial only to fulfill the demands of EV proprietors but also to relieve range anxiety and improve user convenience, thereby facilitating wider EV adoption. This paper provides a comprehensive global analysis of charging station infrastructure, exploring international standards and regulations, various charging modes, the key parameters of leading electric vehicles, and the importance of RE deployment and ES solutions.